Atypical Feeding and Drainage of Dural AV Fistula - Mehmet Sirik; Bulent Petik; Deniz Colak; Sukru Mehmet Erturk; Mehmet Karatas (Journal of the Belgian Society of Radiology, 2016)
Dural arteriovenous fistulas (DAVF) are frequent causes of pulsatile tinnitus. Color Doppler sonography may play a useful, complementary role to CTA/MRA and digital subtraction angiography (DSA) in the assessment of these anomalies’ characteristics, such as an ipsilateral increased flow volume and a low resistive index. In this article, we report a case of DAVF first detected with Color Doppler sonography that displayed an uncharacteristic venous drainage pattern.